Racism in History classes - Corrêa, Michelle Viviane Godinho (Revista Hipótese, 2016)
This article aims to expose the data collected in two classes in two public school during lessons of the history of Brazil in Belo Horizonte. In this sample several images and denominations given to afro-descendants can be observed. Those manifestations have been consolidated in the social imaginary of our society and the teacher is challenged to face these questions that must be overcome. Through a phenomenological observation, we seek to understand the context in which these manifestations appear and how to relate them to the every day life of the subjects involved.
Keywords: Racism; Classroom; History